Implementasi Kebijakan Penagihan Pajak Terhadap Wajib Pajak Pailit di KPP Pratama Gresik - Giyanto, Bambang; Rajab, Ridwan; Hernanda Puspitasari, Dewi (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2025)
Taxes are the primary source of state revenue, contributing approximately 80% to the financing of the State Budget (APBN). However, the effectiveness of tax collection faces significant challenges, particularly in cases involving bankrupt taxpayers. This study aims to analyze the implementation of tax collection policies for bankrupt taxpayers at the Gresik Primary Tax Office (KPP Pratama Gresik) using the policy implementation theory developed by Mazmanian and Sabatier. The findings reveal that the realization rate of tax receivables in bankruptcy cases remains very low, at only around 18%. Key obstacles include regulatory complexity, weak policy structure, and limited technical capacity among tax officers. The tractability of the problem is low due to overlapping regulations between the Law on General Provisions and Tax Procedures (UU KUP) and the Bankruptcy Law. Meanwhile, the ability of policy decisions to structure implementation is inadequate due to the absence of standardized technical guidelines. This research recommends regulatory harmonization and enhanced technical capacity among implementers to ensure that tax collection from bankrupt taxpayers is conducted more effectively and fairly, supporting long-term fiscal sustainability.